Problems and Prospects of the Land Market Development in Russia - Barsukova, Galina Nikolayevna; Radchevskiy, Nikolai Mikhailovich; Saifetdinova, Natalia Rafailovna; Bershitskiy, Yuriy Iosifovich; Paramonov, Petr Filippovich (International Journal of Economics and Financial Issues, 2017)
The article formulates the problem of land ownership formation, and land market development. It has been found that the theory of institutional changes has a high methodological potential for the studies of land relations. It is proposed to use the institutional approach to the study of land ownership and transaction costs, whose growth hinders the development of the land market in Russia. According to the theory of R. Coase, the significance of transaction costs for the land market development was shown, and the conclusion about the need to reduce them was made. Taking into account the objective limitations of turnover of agricultural land category, it was proposed to assess the potential of development of the various sectors of land market in the country using the growth curve methodology. There was justified the expediency of evaluating the public and private sector of land market in terms of turnover, which expresses the ratio of the total land area of transactions in the segmental markets to the total amount of land in the definite form of ownership. The land transactions were evaluated and the forecast of the land market development in the Russian Federation was defined. Keywords: form of ownership, land market, institutional approach, transaction costs, market infrastructure, market value of land, JEL Classifications: K11, Q15